The certainty and the safety as fundamental values in the declaration of the Right and in the accomplishment of the Justice, and the way of reaching them (Revista da Faculdade de Direito, Universidade de São Paulo, 1999)
The article intends to show that, in the declaration of law in the concrete case, which will always result from that which is provided in an abstract manner in the legal rules whether of material or Procedural Law, enforced through prior teleological and systematic interpretation of same, the court decisions should guide themselves by the general principles of the science of law, which will be the control valves for the correct enforcement of the same legal rules which shall govern the same concrete case. Thus, not only will Justice be achieved, which is to be understood as the lawfully founded prevalence of one of the conflicting interests to the detriment of the other, but also legal certainty and security, which are values intimately related to the value of Justice, with the consequent uniformity of case law, apart from everything else. An attempt was also made to illustrate the ideas put forward with comments on two decisions held by two different high courts in the State of São Paulo.